1972
DOI: 10.1002/1097-0142(197211)30:5<1241::aid-cncr2820300515>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for metastatic intracranial neoplasm

Abstract: The course of 167 patients with a surgically treated metastatic brain neoplasm is reviewed. The most common primary site was lung (37%) followed by breast and skin. Three quarters of the patients had a previous history of malignancy, and one third had a tumor visible on chest roentgenogram. Operative mortality was below 10% after 1950, and was lowest when complete tumor removal was achieved. Corticosteroids had little effect on operative mortality. Median survival after surgery was 6 months, but seven patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…Previous studies have suggested that patients with multiple brain metastases do not benefit from more aggressive treatment such as resection in addition to WBRT [9,24]. In contrast to patients with multiple lesions, RPA class 1 and 2 patients with single or only a few brain metastases may benefit from intensified treatment regimens such as additional resection of metastases or radiosurgery.…”
Section: Prognostic Factormentioning
confidence: 99%
“…Previous studies have suggested that patients with multiple brain metastases do not benefit from more aggressive treatment such as resection in addition to WBRT [9,24]. In contrast to patients with multiple lesions, RPA class 1 and 2 patients with single or only a few brain metastases may benefit from intensified treatment regimens such as additional resection of metastases or radiosurgery.…”
Section: Prognostic Factormentioning
confidence: 99%
“…Sixty to 70 percent of metastatic lesions are generally believed to be multiple. 19,20 Cases of solitary metastasis are few and, even if metastatic brain lesions are operable, a resection cannot be performed in many patients because of their poor general condition. Yamamoto et al 21 suggested that, to be suitable for surgery, metastatic brain tumors should satisfy some of the following requirements: (1) a single metastatic lesion in the brain, or if multiple, the lesions should be resectable by a single surgical intervention; (2) a metastatic lesion located in an operable site; (3) no metastasis to any other organs; (4) a good general condition of the patient.…”
Section: Figmentioning
confidence: 99%
“…9,19,24,25 Harr and Patterson 19 reported a mean postoperative survival of 6 months. Kobayashi et al 24 reported that, in resected cases, a 3-month survival was 61.5% and 6-month survival was 41.0%.…”
Section: Figmentioning
confidence: 99%
“…Modern advances, including the use of corticosteroids and neuro-anesthesia, the advent of computed tomography and magnetic resonance imaging, the use of the microscope, and the development of intraoperative ultrasound, stereotactic localization, and cortical mapping, have significantly reduced operative mortalities and morbidities. Post-operative mortality is more often due to uncontrolled systemic cancer, but comparisons of results from gross total removal and partial removal of brain metastases indicate that the former yields the lowest rate of operative mortality and that the 30-day mortality risk may be doubled in cases of partial removal [34]. Non-fatal complications such as hematomas, wound infections, pseudomeningocele formations, as well as surgery-induced neurologic impairments, are usually transient events.…”
Section: Complicationsmentioning
confidence: 99%